Case report: A case of anti-laminin 332 mucous membrane pemphigoid associated with severe pharyngolaryngeal involvement - Quattri, Eleonora; Zussino, Martina; Lauro, Wanda; Berti, Emilio; Marzano, Angelo Valerio; Genovese, Giovanni (Frontiers in Medicine, 2022)
Abstract A 74-year-old woman presented with a 30-day history of blisters and erosions in the oral cavity, trunk, and left eye conjunctival mucosa, also reporting a weight loss of 15 kg in the last three months. Histopathological examination showed subepidermal blisters and lymphocytic infiltrates with rare eosinophils in the superficial dermis. Direct immunofluorescence showed linear deposits of IgG and C3 along the dermal-epidermal junction and salt-split skin indirect immunofluorescence confirmed the presence of linear deposits of IgG along the blister floor. Indirect immunofluorescence revealed antibodies against laminin 332 using recombinant laminin 332 expressed in human HEK293 cells, and commercial ELISA kits (Euroimmun, Padova, Italy) did not reveal antibodies against BP230 and BP180 antigens. Anti-laminin 332 mucous membrane pemphigoid (MMP), a condition often associated with a hidden neoplasm, was diagnosed. In our case, the paraneoplastic nature of MMP was excluded. Thus, topical treatment with triamcinolone acetonide 0.1% in orabase once daily for 30 days, oral prednisone 0.75 mg/kg/day and rituximab were started to relieve symptoms. Conjunctival, nasal and oral erosions improved, as well as skin lesions, but later the patient was tracheotomized due to respiratory distress linked to the appearance of pharyngolaryngeal synechiae.